PERAN KEPUASAN PELANGGAN MEMEDIASI KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN - sayoga, putu ogi; Suasana, I Gusti Agung Ketut Gede (E-Jurnal Manajemen; Vol 11 No 8 (2022)DO - 10.24843/EJMUNUD.2022.v11.i08.p07, 2022)
This research was conducted at the Deltra Penelokan Store, Kintamani, Bangli Regency. The number of samples taken as many as 108 people, the respondents' criteria are men or women who shop at Deltra, who have a high school education or the equivalent and shop more than 2 times, with probability sampling method, especially simple random sampling. Data was collected through interviews and observations. The analysis technique used is multiple linear regression. Based on the results of the analysis found that service quality has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty, customer satisfaction is able to mediate the effect of service quality on customer loyalty in other words service quality has an indirect effect on customer loyalty through customer satisfaction. Keywords: satisfaction, quality, customer loyalty